Study of the strength characteristics and radiation resistance of thin-film coatings based on CuX (X=Bi, Mg, Ni) - Shlimas, D; Kozlovskiy, A. L.; Kaliekperov, M. E.; Kadyrzhanov, K. K.; Uglov, V. V. (Eurasian Journal of Physics and Functional Materials, 2026)
The paper presents the results of changes in the strength characteristics of thin film coatings based on compounds of copper-bismuth, copper-magnesium, copper-nickel. The dependences of the influence of the phase composition on the strength characteristics, such as the coefficient of friction, bending strength and impact coefficient, are established. The effect of irradiation with helium ions with a high radiation dose of 1015-1017 ion/cm2 on the strength characteristics is evaluated. It is shown that an increase in the radiation dose leads to a decrease in strength properties due to the appearance of a large concentration of defects in the structure. Recommended Citation Shlimas, D. I.; Kozlovskiy, A. L.; Kaliekperov, M. E.; Kadyrzhanov, K. K.; and Uglov, V. V. (2020) "Study of the strength characteristics and radiation resistance of thin-film coatings based on CuX (X=Bi, Mg, Ni)," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 5. DOI: https://doi.org/10.29317/ejpfm.2020040305